General Systems Theory and Remanufacturing / Teoría general de sistemas y remanufactura - Rodrigues, Glauco Oliveira; Schuch, Crislei Daiana Oliveira Siqueira; Antunes, Marcelo Cassanta; Piovesan, Carlos (ID on line. Revista de psicologia, 2022)
The general systems theory emerged from the works of the Austrian biologist Ludwig von Bertalanffy, published between 1950 and 1968. This theory has as its main purpose, to analyze the nature of systems and the interrelationship between these systems and different spaces, as well as the interrelationship of its parts. It also analyzes the fundamental laws of systems. Remanufacture, in turn, is an industrial process that consists of the steps of dismantling the discarded or already used product, the remanufacturing process includes the steps of cleaning its parts, repairing, or replacing damaged parts. This article aims to analyze the prose academic productions of the last ten years. Bibliometric analysis was performed through the Web of Science platform. : La teoría general de sistemas surgió a partir de los trabajos del biólogo austriaco Ludwig von Bertalanffy, publicados entre 1950 y 1968. Esta teoría tiene como objetivo principal analizar la naturaleza de los sistemas y la interrelación entre estos sistemas y diferentes espacios, como así como la interrelación de sus partes. También analiza las leyes fundamentales de los sistemas. La remanufactura, a su vez, es un proceso industrial que consiste en los pasos de desmantelar el producto desechado o ya usado, el proceso de remanufactura incluye los pasos de limpiar sus partes, reparar o reemplazar las partes dañadas. Este artículo tiene como objetivo analizar las producciones académicas en prosa de los últimos diez años. El análisis bibliométrico se realizó a través de la plataforma web of Science.